Sacralisation of the female image during wartime in Ukraine and its reflection in graphic artworks - Horichko, Yaryna (Art and Design, 2025)
The purpose of the study was to analyse artistic strategies and visual mechanisms involved in the sacralisation of the female image in Ukrainian wartime graphics, particularly in posters, engravings, and illustrations from the periods of the world wars and contemporary armed conflicts. The study explored artistic techniques, symbolism, and iconographic traditions that shaped the sacral representation of women in war-related art. The methodological approach was based on a systematic analysis of artistic methods, compositional solutions, colour strategies, and stylistic features of the works examined. Findings demonstrated that the sacralisation of the female image in Ukrainian wartime graphics relied on established visual codes, which had evolved under the influence of socio-cultural and technological changes in art. A comparative analysis of Ukrainian, Soviet, German, French, and British graphic materials identified key tendencies in the depiction of the female figure, including their heroisation, mythological and religious attributes, and the use of artistic means to construct national identity. In contemporary Ukrainian graphic design, the sacred female image underwent a considerable transformation, shifting away from traditional allegorical frameworks towards expressive and personalised visual approaches. Increasingly, the female figure was portrayed not only as a national symbol or guardian figure but also as an equal participant in combat, thereby altering the visual narrative of wartime art. Contemporary posters frequently employed colour schemes combining blue and yellow, red and black, or stark monochromatic contrasts, enhancing the emotional resonance of the imagery. Digital technologies were widely utilised, enabling the integration of traditional graphic techniques with new visual strategies, including dynamic compositions, animated elements, and the adaptation of iconographic motifs to contemporary contexts. The study demonstrated that sacralisation of the female image in graphic art was achieved through the synthesis of traditional symbols, innovative visual strategies, and the reinterpretation of historical archetypes within a contemporary framework. Visual representation of women in wartime art continued to evolve, incorporating new stylistic tools and artistic concepts that expanded the communicative power and cultural impact of graphic design in the context of national identity and cultural resistance.